Cardiac Reconstructions with Allograft Tissues - Hopkins, Richard A. (Springer New York : Imprint: Springer, 2005)
Cryopreserved allograft tissues are now standard materials for the reconstructive cardiac surgeon. Since publication of the first edition ("Cardiac Reconstructions with Allograft Valves") in 1989, the field has progressed dramatically with increased clinical use of cardiovascular allograft tissues, with the development of new surgical techniques, and with advances in the understanding of the fundamentals of valve transplantation biology and cryopreservation. As a result, over two-thirds of the present volume represents new material. Fifty-six authors bring their expertise to thirteen comprehensive, lavishly illustrated sections which discuss the principles of the use of homograft valves, major clinical series of homograft valves for both left and right ventricular outflow tracts, cryopreserved allograft tissue for cardiac reconstruction, cell biology of heart valve leaflets, cryobiology of heart valve preservation, morphological, biochemical, and explant pathology studies of allograft heart valves, allograft valve banking, as well as detailed explanation of surgical techniques for valve and root methods for left and right ventricular outflow tract reconstructions, the Ross operation and variants, and complex reconstructions. A final section presents potential future directions for the field. Over 400 illustrations, created expressly for this book, depict the surgical techniques from the perspective of the surgeon standing at the operating table. All surgeons performing pediatric and/or adult valve replacements and reconstructive cardiac surgeries will benefit from the described methods. Cardiothoracic residents and cardiologists will also find the text useful. It will provide the surgeon with an enhanced understanding of the biological and material properties of allografts and increased familiarity with the range of surgical techniques applicable for the use of these valves, particularly in the successful management of challenging cardiac reconstructions.>.